Biocultural Diversity Conservation: A Global Sourcebook - Jose Martinez-Reyes (Ethnobiology Letters, 2012)
Review of Biocultural Diversity Conservation: A Global Sourcebook. Luisa Maffi and Ellen Woodley. 2010. Earthscan, London. Pp. 304. $57.95 (paperback). ISBN 978-1-84407-921-6.